Studi Literatur Gambaran C-Reactive Protein Pada Penderita Hipertensi - Umi Fadilah; Djoko Priyatno (Jaringan Laboratorium Medis, 2020)
Hypertension is called the silent killer, often known after complications occur. Based on the results of Riskesdas in 2018, the prevalence of hypertension in Indonesia at age ≥18 years increased to 34.1% in 2018. Endothelial injury caused by hypertension triggers inflammation or chronic inflammation of the arterial wall. Evidence of an inflammatory process is the discovery of C-Reactive Protein (CRP) which is a marker of inflammation from non-bacterial infections.The purpose of this study to knowing the description of C-Reactive Protein in patients with hypertension through research by Fadhliani (2016), Dolly (2018), Harahap (2019). This paper is a summary of  research result, with the criteria for systematic study research through a systematic review approach. In patients with hypertension according to research Fadhliani (2016) obtained as much as 23% C-Reactive Protein positive and 77% C-Reactive Protein negative. In the Harahap study (2019) of 30 people with hypertension, 12 people (40%) had positive C-Reactive Protein and 18 people (60%) had negative C-Reactive Protein. Whereas in the study of Dolly (2018) the average level of hs-CRP in hypertensive patients is 4, 85 mg / L. According to Dolly's research (2018) in patients with hypertension for > 1 year have higher levels of hs-CRP compared to patients with hypertension for a period of ≤1 years. Examination of C-Reactive Protein (CRP) in patients with hypertension in the Harahap study (2019) showed positive CRP results dominated by subjects with age ≥ 50 years as many as 8 people (27%).